Fractional optical solitons for the conformable space-time nonlinear Schrodinger equation with Kerr law nonlinearity - İnç, Mustafa; Yusuf, Abdullahi; Aliyu, Aliyu Isa; Baleanu, Dumitru (Springer, 2018)
In this work, we obtain new soliton solutions for the conformable space-time nonlinear Schrodinger equation (CSTNLSE) with Kerr law nonlinearity. Two integration schemes which are projective Ricatti and extended Jacobi elliptic function methods are applied to reach such solutions. The constraints conditions for the existence of soliton solutions are reported. Numerical simulations for some of the obtained solutions are presented.
Keywords: CSTNLSE; PR method; EJEF method and conformable derivative